AKTIVITAS PENGHAMBATAN PEMBENTUKAN BATU GINJAL (Antinefrolithiasis) EKSTRAK ETANOL DAUN GEDI MERAH (Abelmoschus moschtus Medik) PADA TIKUS PUTIH JANTAN - Triana Riandani Djamhuri; Yuliet Yuliet; Khildah Khaerati (Universitas Tadulako, 2016)
Red Gedi (Abelmoschus moschatus Medik) is a plant found only in tropical climate areas such as Africa and Asia. Some people’s experience in Manado stated that red gedi plants can be used to treat various types of disease, one of them was kidney stones. Therefore, this study aimed to determine the activity and the effective dose of red gedi leaf extract as an inhibitor of kidney stone formation. The extract was prepared by maceration using ethanol 96%. Inhibitory activity test of kidney stone formation was done by firstly dividing the labrats into 6 groups. Each group consisted of 3 male rats. Both the first group (Normal control) and the second group (Negative control) weregiven Na.CMC 0.5%; the third group (Positive control) was given Batugin Elixir at a dose of 2.7 ml/kgBW; while the fourth, fifth, and sixth were respectively given red gedileaf extract at doses of 50, 100, and 150 mg/kgBW. After 2 hours, all treatment groups were induced with0.75% of ethylene glycol and 2% of ammonium chloride except for the normal control. Ratio of kidney weight and the level of calcium were then measured and calculated. Data obtained were statistically analyzed using ANOVA (Analysis Of variance) and continued with LSD (Least Significantly Difference). It can be concluded that ethanol extract of red gedileaves had inhibitory activity of kidney stones formation in all dose variation and the most effective one was at a dose of 150 mg/kgBW